(untitled) (Cuea Journal of Business and Economics, 2024)
This empirical review examines the effects of cross-border mergers and acquisitions (M&As) synergies on the financial performance of commercial banks, with fintech as a mediating variable. The study synthesizes findings from empirical research on listed commercial banks worldwide that engaged in cross-border M&As between 2010-2022. Results consistently show that M&As synergies led to improved profitability, shared resources, and enhanced liquidity. Financial and operational synergies demonstrated significant positive impacts on bank performance metrics. Emerging evidence suggests fintech capabilities play an important mediating role, strengthening the relationship between M&As synergies and bank performance. The review concludes that cross-border M&As, when leveraged effectively alongside fintech innovation, can substantially improve commercial bank financial performance and competitiveness in the evolving global banking landscape. However, challenges in realizing managerial synergies and navigating cultural differences in cross-border contexts remain significant considerations for successful M&As implementation. This review provides valuable insights for bank executives, regulators, and policymakers navigating the complex landscape of international banking and fintech integration.